A global meta-analysis of the ecological impacts of alien species on native amphibians. Issue 1897 (27th February 2019) - Nunes, Ana L.; Fill, Jennifer M.; Davies, Sarah J.; Louw, Marike; Rebelo, Alexander D.; Thorp, Corey J.; Vimercati, Giovanni; Measey, John
Abstract : The exponential increase in species introductions during the Anthropocene has brought about a major loss of biodiversity. Amphibians have suffered large declines, with more than 16% considered to be threatened by invasive species. We conducted a global meta-analysis of the impacts of alien species on native amphibians to determine which aspects of amphibian ecology are most affected by plant, invertebrate, fish, amphibian, reptile, or mammal introductions. Measures of fitness were most strongly affected; amphibian performance was consistently lower in the presence of alien species. While exposure to alien species caused a significant decrease in amphibian behavioural activity when compared with a no species control, this response was stronger towards a control of native impacting species. This indicates a high degree of prey naiveté towards alien species and highlights the importance of using different types of controls in empirical studies. Alien invertebrates had the greatest overall impact on amphibians. This study sets a new agenda for research on biological invasions, highlighting the lack of studies investigating the impacts of alien species on amphibian terrestrial life-history stages. It also emphasizes the strong ecological impacts that alien species have on amphibian fitness and suggests that future introductions or global spread of alien invertebrates could strongly exacerbate current amphibian declines.